AI: The South Kalimantan Provincial Government's Perspective on Government Internal Audit - Hardy, Enny; Mediaty, Mediaty; Arifuddin, Arifuddin; Tegar Wicaksana, Dimas; Maulida, Sri (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2025)
The effectiveness and efficiency of internal government monitoring could be greatly improved by the development of artificial intelligence (AI). Nonetheless, the adoption of AI is greatly impacted by human attitudes and intentions. Investigating the effects of the General Attitudes Toward AI Scale (GAAIS) on the Government Internal Audit (APIP) BPKP and Inspectorate's Intention to Use (ITU) AI is the aim of this study. The government's internal control system was surveyed using a quantitative methodology. Surveys evaluating GAAIS and ITU AI were used to gather data. To investigate the relationship between variables, data analysis was conducted using basic linear regression utilizing the (SPSS) software. Examining the general attitude of APIP toward the intention to utilize AI (GAAIS) is the innovative aspect of this study. The findings demonstrated that GAAIS significantly and favorably impacted AI ITU. This suggests that the apparatus's intention to use AI increases with its good attitude toward it. Perceived utility and usability are the main determinants of ITU, although fear of AI serves as a barrier that can be overcome with socialization and training.